Action-oriented knowledge for sustainable management of organic soils in Finnish agriculture - Huan-Niemi, Ellen; Huttunen, Suvi; Paloviita, Ari; Puupponen, Antti; Lehtonen, Heikki; Niemi, Jyrki (Agricultural and Food Science, 2023)
Agriculture is a contributing force to climate change due to unsustainable changes in land use with the usage of peatlands for food production in Finland. The use of organic soils in food production is a complex and politically driven issue, thus multistakeholder and participatory approaches to policy development, implementation and evaluation are essential. This study is integrating qualitative and quantitative methods in an iterative process to produce action-oriented knowledge for supporting actions to sustainably manage peatlands and reduce the enormous greenhouse gas emissions from agricultural peatlands. This study has engaged inter-disciplinary researchers and transdisciplinary actors in the Finnish food system via farmers, regional and ministry officials, food industry representatives along with education and research representatives to produce action-oriented knowledge for sustainability. The results indicate that actions are needed to develop a shared understanding between relevant actors and stakeholders in the food system to create activities and effective policy measures to remove peatlands from active production in Finland. Therefore, there is a necessity to identify and define incentives from both the public and private sectors to remove peatlands from food production, and thus reducing greenhouse gas emissions from agriculture. Interventions that account for local, regional, and national perspectives should be co-created among the inter-disciplinary researchers and transdisciplinary actors in the food system to generate transformative and system-wide change in the transition towards a low-carbon society.